Developing a parent vocabulary checklist for young Indigenous children growing up multilingual in the Katherine region of Australia's Northern Territory. (2nd September 2020) - Jones, Caroline; Collyer, Eugenie; Fejo, Jaidine; Khamchuang, Chantelle; Painter, Anita; Rosas, Lee; Mattock, Karen; Dunajcik, Alicia; Escudero, Paola; Dwyer, Anne
Abstract: Purpose: The aim of this study was to develop a checklist to assess vocabulary development in Indigenous Australian children, with a local focus on Indigenous Australian children growing up in the towns and communities of the Katherine Region in the Northern Territory of Australia. In this region, many families are multilingual and/or multidialectal and children's home languages include varieties of Aboriginal English, Kriol, traditional Aboriginal languages, and/or other languages. Method: Over four years, a checklist was iteratively developed from parent interviews, comparisons of potential items to the content and structure of the Communicative Development Inventories (CDI): Words & Gestures (Short Form), team discussions and pilot testing with 33 parents of infants aged 0–4 years. Result: The Early Language Inventory (ERLI) checklist offers new content compared with the CDI: Words & Gestures (short form) and the OZI (Australian English CDI, long form). Initial data from 33 parents suggests the checklist has desirable features: scores correlated positively with age and related to word combining, reaching ceiling around 3 years of age for many children. Infants whose parents had concerns tended to have lower scores. Conclusion: ERLI is a new local adaptation of the CDI (Words & Gestures) for assessing early communication among Indigenous infants growing up in the Katherine region of the Northern Territory, Australia.